Knowing full well - Sosa, Ernest (Soochow University lectures in philosophy, 2011)
Explaining the nature of knowledge, this book presents an account of the author's views on epistemic normativity as a form of performance normativity on two levels. It shows how experience should be understood if it is to figure in the epistemic competence that must be manifest in the truth of any belief apt enough to constitute knowledge.
Keywords: Virtue epistemology; normatiivisuus; tietoteoria